Polymorphisms of the artemisinin resistant marker (K13) in Plasmodium falciparum parasite populations of Grande Comore Island 10 years after artemisinin combination therapy. Issue 1 (December 2015) - Huang, Bo; Deng, Changsheng; Yang, Tao; Xue, Linlu; Wang, Qi; Huang, Shiguang; Su, Xin-zhuan; Liu, Yajun; Zheng, Shaoqin; Guan, Yezhi; Xu, Qin; Zhou, Jiuyao; et al.
Abstract Background Plasmodium falciparum malaria is a significant public health problem in Comoros, and artemisinin combination therapy (ACT) remains the first choice for treating acute uncomplicatedP. falciparum . The emergence and spread of artemisinin-resistantP. falciparum in Southeast Asia, associated with mutations in K13-propeller gene, poses a potential threat to ACT efficacy. Detection of mutations in theP. falciparum K13-propeller gene may provide the first-hand information on changes in parasite susceptibility to artemisinin. The objective of this study is to determinate the prevalence of mutant K13-propeller gene among theP. falciparum isolates collected from Grande Comore Island, Union of Comoros, where ACT has been in use since 2004. Methods A total of 207P. falciparum clinical isolates were collected from the island during March 2006 and October 2007 (n = 118) and March 2013 and December 2014 (n = 89). All isolates were analysed for single nucleotide polymorphisms (SNPs) and haplotypes in the K13-propeller gene using nested PCR and DNA sequencing. Results Only three 2006–2007 samples carried SNPs in the K13-propeller gene, one having a synonymous (G538G) and the other having two non-synonymous (S477Y and D584E) substitutions leading to two mutated haplotypes (2.2 %, 2/95). Three synonymous mutations (R471R, Y500Y, and G538G) (5.9 %, 5/85) and 7 non-synonymous substitutions (21.2 %, 18/85) with nine mutated haplotypes (18.8 %, 16/85) were found in isolates from 2013 to 2014. However, none of the polymorphisms associated with artemisinin-resistance in Southeast Asia was detected from any of the parasites examined. Conclusion This study showed increased K13-propeller gene diversity amongP. falciparum populations on the Island over the course of 8 years (2006–2014). Nevertheless, none of the polymorphisms known to be associated with artemisinin resistance in Asia was detected in the parasite populations examined. Our data suggest thatP. falciparum populations in Grande Comore are still effectively susceptible to artemisinin. Our results provide insights intoP. falciparum populations regarding mutations in the gene associated with artemisinin resistance and will be useful for developing and updating anti-malarial guidance in Comoros.